Integrating Artificial Intelligence in Stroke Rehabilitation: Current Trends and Future Directions; A mini review. - Ayesha Afridi; Sumaiyah Obaid; Neha Raheel; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Rehabilitation following a stroke faces challenges in offering customized treatment and attaining the best possible outcomes. The utilization of artificial intelligence (AI) presents transformative solutions that have the potential to revolutionize existing practices. This minireview discusses the use of AI in rehabilitation after stroke, in form of customized intervention, task-specific training with robotics, real time monitoring by wearable devices and remote monitoring through tele rehabilitation. Despite the recent advances, issues such as algorithm bias, concerns about data security, and access disparities remain. Future directions include creating predictive analytics for tailored stroke therapies, incorporating virtual reality for increased participation, and assuring ethical and equitable distribution. Collaborative efforts are necessary to address these challenges and advance AI-driven stroke therapy. This review highlights the potential of AI to revolutionize stroke rehabilitation outcomes through interdisciplinary collaboration and ethical implementation. Keywords: Artificial Intelligence, Rehabilitation, Stroke, Technology, outcomes, recent advances